2007
DOI: 10.1523/jneurosci.2551-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Reward Bias in Humans: Fronto-Parietal Networks and a Role for the Catechol-O-Methyltransferase 158Val/ValGenotype

Abstract: The tendency to choose lesser immediate benefits over greater long-term benefits characterizes alcoholism and other addictive disorders. However, despite its medical and socioeconomic importance, little is known about its neurobiological mechanisms. . These studies assume "hot" and "cool" response selection systems, with the hot system proposed to generate impulsive choices in the presence of a proximate reward. However, to date, brain regions in which the magnitude of activity during decision making reliably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
274
6
7

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(321 citation statements)
references
References 79 publications
33
274
6
7
Order By: Relevance
“…This area was less responsive to food receipt in OB individuals (Gearhardt et al, 2011), and it was hypothesized that lower response in that region could be associated with reduced behavior control and suppression of reward response (Boettiger et al, 2007;Elliott et al, 2000;Goldstein et al, 2007). Reduced lateral orbitofrontal cortex activation in OB may then be associated with reduced, and increased activation in AN could be associated with increased impulse control to reward presentation.…”
Section: Discussionmentioning
confidence: 99%
“…This area was less responsive to food receipt in OB individuals (Gearhardt et al, 2011), and it was hypothesized that lower response in that region could be associated with reduced behavior control and suppression of reward response (Boettiger et al, 2007;Elliott et al, 2000;Goldstein et al, 2007). Reduced lateral orbitofrontal cortex activation in OB may then be associated with reduced, and increased activation in AN could be associated with increased impulse control to reward presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Pine et al (2010) demonstrated that relative to placebo, control subjects given the dopamine precursor L-dopa showed consistent increases in delay discounting. In addition, the genotype for the dopamine-degrading enzyme catechol-Omethyltransferase (COMT) correlates with levels of impulsivity: subjects tend to be more impulsive if they have alleles encoding the more enzymatically active form of COMT (Boettiger et al, 2007). Because COMT represents the primary route for dopamine degradation in frontal cortex (Gogos et al, 1998), lower dopamine tone in frontal cortex may therefore predispose some individuals to greater impulsivity.…”
Section: Introductionmentioning
confidence: 99%
“…The orbitofrontal cortex (OFC), a region within the prefrontal cortex (PFC), mediates several aspects of learning, including choice behavior (Boettiger et al, 2007;Bokura et al, 2001;Ramus and Eichenbaum, 2000;Roesch et al, 2007a;Schoenbaum et al, 1998), reversal learning (Dalley et al, 2004;McGaughy et al, 2008;Roesch et al, 2007b;Thorpe et al, 1983) and the development of expectancies/predictions (Ito et al, 2001;Tremblay and Schultz, 1999) about appetitive and aversive stimuli. Current thinking suggests that the OFC, with its extensive array of sensory and limbic derived inputs, mediates learning processes and specifically choice behavior by providing a place for incoming information to be integrated and by attributing salience to relevant environmental cues.…”
Section: Introductionmentioning
confidence: 99%